Machinability analysis of LM26 aluminium metal matrix composites reinforced with graphite and fly ash using the AWJM process - C. Prakash; S. Selvakumar; D. Manikandan; Krishnaraj Ramaswamy (Scientific Reports)
Abstract The incorporation of various reinforcements in aluminium composites markedly improves their thermal, mechanical, and wear characteristics when compared to composites with a single reinforcement. Nevertheless, heightened hardness presents challenges in machining, rendering traditional methods less efficient for obtaining high-quality cuts. This study explores the application of Abrasive Water Jet Machining (AWJM) on aluminium alloy LM26 hybrid composites that are reinforced with graphite and fly ash, which were manufactured through stir casting. AWJM is assessed as a viable machining technique to tackle the challenges presented by these advanced composites. The analysis focuses on key process parameters, including transverse speed, stand-off distance, and abrasive flow rate, to evaluate their impact on essential output responses such as surface roughness, material removal rate (MRR), and overcut error. A systematic experimental design utilizing an L27 orthogonal array is implemented to thoroughly examine the influences of various parameters. Response Surface Methodology (RSM) serves as a vital tool for statistical analysis and optimization, facilitating an in-depth exploration of parameter interactions and their influence on machining performance. The results offer important perspectives on enhancing AWJM parameters for hybrid aluminium composites, leading to better machining precision and efficiency. The ideal machining parameters were determined to be an abrasive flow rate of 440 g/min, a traverse speed of 300 mm/min, and a stand-off distance of 1.50 mm, leading to a peak MRR of 1.201 g/sec and a minimum surface roughness (Ra) of 2.018 µm. The investigation highlights AWJM’s proficiency in processing high-hardness materials while preserving favorable surface qualities. The findings enhance manufacturing methods for reinforced aluminium composites, facilitating their wider use in aerospace, automotive, and other high-performance sectors.